1994
DOI: 10.1007/s00585-994-0139-8
|View full text |Cite
|
Sign up to set email alerts
|

A study of quasi-periodic ELF-VLF emissions at three Antarctic stations: evidence for off-equatorial generation?

Abstract: Abstract. The spatial extent and temporal behaviour of quasi-periodic (QP) intensity modulations of 0.5-2 kHz ELF-VLF signals were investigated in a comparative study of data collected at the Antarctic stations of South Pole (L=14), Halley (L=4), and Siple (L=4). Frequently, the waveforms of ELF-VLF signals simultaneously received at each site were identical. Although of similar frequency structure, the waveforms of the accompanying Pc3 magnetic pulsations did not show a one-to-one association. Whereas both ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 0 publications
6
28
0
Order By: Relevance
“…The near‐noon peak in the diurnal profile of QP 1 and QPPE 1 events is consistent with the observations of Morrison et al [1994], again supporting the commonly held view that Pc3‐4 magnetic pulsations are the driver of the observed modulations of ELF/VLF waves (type I QPs). As Smith et al [1998] noted, however, the generation of type II QP events is not well understood.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The near‐noon peak in the diurnal profile of QP 1 and QPPE 1 events is consistent with the observations of Morrison et al [1994], again supporting the commonly held view that Pc3‐4 magnetic pulsations are the driver of the observed modulations of ELF/VLF waves (type I QPs). As Smith et al [1998] noted, however, the generation of type II QP events is not well understood.…”
Section: Discussionsupporting
confidence: 86%
“…This confirmation of the simultaneity of most if not all QP and PE events lends support to the idea advanced by Morrison et al [1994] that each site is seeing a signal from the same relatively localized, ducted whistler event in the magnetosphere. The range of latitudes available in this study thus gives us clues about the L ‐shells on which these events originate.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…QP1 is more widely referred to in the literature (e.g., Kimura, 1974;Sato and Fukunishi, 1981;Bespalov and Kleimenova, 1989;Sazhin and Hayakawa, 1994;Manninen et al, 2012). However, there have been relatively few papers analysing QP2 emissions and described their behaviour (Ho, 1973;Morrison et al, 1994;Smith et al, 1998;Engebretson et al, 2004). Based on Antarctic observations, these authors concluded that QP2 are most common in austral summer under conditions of quiet geomagnetic activity, their diurnal maximum of occurrence is near noon, and the period of separated VLF bursts repetition ranged from ∼20 s to ∼100 s. The QP emissions showed good conjugateness and the elements of QP emissions appeared simultaneously at the conjugate stations.…”
Section: Introductionmentioning
confidence: 99%